Development of DNA Molecular Markers for the varietal identification of Eucheuha, an economically important seaweed species from Sabah, Malaysia - Ann Anton, Datin (Universiti Malaysia Sabah, 2012)
Kappaphycus and Eucheuma seaweeds are economically important seaweed species in Sabah and currently are the most widely cultivated seaweed for commercial carrageenan production. The physical morphology of the seaweed is greatly influenced by its genetic make-up and environmental factors which has led to confusion in the taxonomy of the species. This study aims to resolve the phylogeny of Kappaphycus and Eucheuma seaweeds based on the nuclear, mitochondrial and chloroplast DNA, and to develop specific primers for the identification of K. alvarezii, K. striatum and E denticulatum. A total of fifteen phenotypes of Eucheuma and Kappaphycus seaweeds were collected from Sebangkat Island, Semporna Sabah. Phylogenetic relationship of the mitochondrial encoded cox1 gene and cox2 -3 spacer, the 18S and ITS regions of the nuclear ribosomal DNA and the plastid RuBisCo spacer of the seaweeds were successfully analyzed. The phylogenetic trees distinctly separated the three seaweed species viz. K. alvarezii, K. striatum and E denticulatum. The results obtained showed some incongruence with the morphological characters data. It was determined that ITS region was the suitable locus for phylogenetic reconstruction and species differentiation for Kappaphycus sp. and E denticulatum. Specific primers for ITS region were designed and developed for rapid and direct identification of K. alvarezi;, K. striatum and E denticulatum using multiplex peR amplification which is based on species-specific amplicons ranging from 144-415 bp. The ITS region contains enough variation to generate unique identifiers at the species level for Kappaphycus sp. and E denticulatum. The outcomes of this study will facilitate in the understanding of the phylogenetic relationship between Kappaphycus and Eucheuma seaweeds in Sabah.